1995
DOI: 10.1159/000173928
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rh-GMCSF and rh-GCSF on Oxygen Free Radical Production by Human Neutrophils and Blood Monocyte-Derived Human Macrophages

Abstract: The in vitro effect of recombinant human granulocyte-macrophage colony stimulating factor (rh-GMCSF) and recombinant human granulocyte colony stimulating factor (rh-GCSF) on oxygen free radical (OFR) generation by human neutrophils and blood monocytes derived human macrophages stimulated with phorbol myristate acetate was investigated and compared. The production of OFR by neutrophils and macrophages was time dependent, and the maximum release of OFR by neutrophils and macrophages was measured 90 and 180 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that endotoxin exposure increases G-CSF release by pulmonary cell populations, including alveolar macrophages, fibroblasts, monocytes, and endothelial cells (52)(53)(54)(55). G-CSF levels are elevated in bronchoalveolar lavage specimens from patients with acute lung injury and contribute to reductions in neutrophil apoptosis in this setting (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that endotoxin exposure increases G-CSF release by pulmonary cell populations, including alveolar macrophages, fibroblasts, monocytes, and endothelial cells (52)(53)(54)(55). G-CSF levels are elevated in bronchoalveolar lavage specimens from patients with acute lung injury and contribute to reductions in neutrophil apoptosis in this setting (2,3).…”
Section: Discussionmentioning
confidence: 99%